Failure of monotherapy in clinical practice in patients with type 2 diabetes: The Korean National Diabetes Program. Issue 5 (9th February 2018) - Jeon, Ja Young; Lee, Soo Jin; Lee, Sieun; Kim, Soo Jin; Han, Seung Jin; Kim, Hae Jin; Kim, Dae Jung; Kim, Young Seol; Woo, Jeong Taek; Ahn, Kyu Jeung; Nam, Moonsuk; Baik, Sei Hyun; et al.
Abstract: Aims/Introduction: We investigated the failure of monotherapy in patients with type 2 diabetes mellitus in real practice settings. Materials and Methods: The Korean National Diabetes Program was a prospective, multicenter observational cohort study of type 2 diabetes mellitus patients in Korea. Of the 3, 950 patients enrolled in the study, we studied 998 who were continuously maintained on monotherapy for at least 90 days at six participating centers. To balance the baseline characteristics of patients in each group, we used propensity matching at a 1:1 ratio (metformin vs sulfonylureas) and 4:1 ratio (metformin vs meglitinides and metformin vs alpha‐glucosidase inhibitors [aGIs]). The hazard ratios (HRs) of treatments (compared with metformin) were determined by Cox's proportional hazards regression modeling. Results: The median follow‐up time was 56 months, and monotherapy failed in 45% of all patients. The annual incidences of failure were 15.6%, 21.3%, 27% and 9.6% in the metformin, sulfonylurea, meglitinide and aGI groups. Compared with metformin, sulfonylureas and meglitinides were associated with higher risks of monotherapy failure (HR 1.39, 95% confidence interval [CI] 1.08–1.80; HR 1.92, 95% CI 1.13–3.27), and aGIs with risks similar to that of metformin (HR 0.80, 95% CI 0.44–1.45). When analyzed by failure type, sulfonylureas, meglitinides and aGIs were associated with a higher risk of a switch to other agents (HR 4.43, 95% CI 2.14–9.17; HR 18.80, 95% CI 6.21–56.93; HR 4.25, 95% CI 1.49–12.13), and aGIs with a lower risk of prescription of add‐on second agents (HR 0.16, 95% CI 0.04–0.64). Conclusions: Metformin was associated with a lower failure risk than were sulfonylureas and meglitinides, but a comparable aGI failure rate. Abstract : The present study demonstrated the annual monotherapy failure rate according to class of anti‐hyperglycemic drug in South Koreans with type 2 DM. This is the first report on failure of aGI monotherapy in clinical practice setting. Compared with metformin, sulfonylureas and meglitinides were associated with higher risks of monotherapy failure and aGIs with risk similar to that of metformin.